Comparisons of magnetic charge and axial charge meson cloud distributions in the PCQM - X. Y. Liu (Nature Portfolio, 2017)
Abstract The meson cloud distributions in r-space are extracted from the nucleon electromagnetic and axial form factors which are derived in the perturbative chiral quark model. The theoretical results indicate that the magnetic charge and axial charge distributions of the three-quark core have the similar distributions in r-space, the magnetic charge distributions of the meson cloud and three-quark core are more or less in the same region and peak at distances of around 0.4 fm, which is in good agreement with the finding of works in the framework of chiral perturbation theory, but the axial charge meson cloud distributes mainly inside the three-quark core.